2019
DOI: 10.1142/s0218271819300192
|View full text |Cite
|
Sign up to set email alerts
|

Are quantum corrections on horizon scale physically motivated?

Abstract: The aim of this short review is to give an overview to non-specialists of recent arguments from fundamental physics in favor and disfavor of quantum corrections to black hole horizons. I will mainly discuss the black hole information paradox, its possible resolutions and shortly address its relevance or irrelevance to astronomy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…In this case, Eq. (25) takes the form a = 2πc T dS , i.e we find the same equation as in (26) valid for black holes, with T dS replacing the black holes temperature T . For the dS universe, Eq.…”
Section: The De Sitter Universesupporting
confidence: 56%
See 1 more Smart Citation
“…In this case, Eq. (25) takes the form a = 2πc T dS , i.e we find the same equation as in (26) valid for black holes, with T dS replacing the black holes temperature T . For the dS universe, Eq.…”
Section: The De Sitter Universesupporting
confidence: 56%
“…For example, in the corpuscular gravity scenario black holes and the de Sitter universe may be explained as quantum coherent states of a large number of gravitons [11,12,13,14,15,16,17,18,19,20,21,22,23]. Recent investigations on the topic have also suggested that quantum gravity corrections may also be relevant at the horizon of astrophysical black holes [26,27,25].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the possibility of quantum-gravity effects at the horizon has been raised, e.g. in [6,44,75,76,84]. In particular, for extended objects like black-hole horizons, a simple power-counting argument based on the local curvature might be misleading.…”
Section: Motivationmentioning
confidence: 99%
“…A sharp way to state a paradox is as a set of hypotheses that are all assumed to be true, but which are in logical contradiction. The paradox is resolved if one can prove one of the hypothesis wrong [82,83,84,85,86]. For the information paradox these hypothesis are basically unitary quantum mechanics, and the assumptions that go into the Hawking calculation [80].…”
Section: Information Paradoxmentioning
confidence: 99%